Kinetic Control in the Regioselective Alkylation of Pterin Sensitizers: A Synthetic, Photochemical, and Theoretical Study - Walalawela, Niluksha (2018)
Alkylation patterns and excited-state properties of pterins were examined both experimentally and theoretically. 2D NMR spectroscopy was used to characterize the pterin derivatives, revealing undoubtedly that the decyl chains were coupled to either the O4 or N3 sites on the pterin. At a temperature of 70°C, the pterin alkylation regioselectively favored the O4 over the N3. The O4 was also favored when using solvents, in which the reactants had increased solubility, namely N,N-dimethylformamide and N,N-dimethylacetamide, rather than solvents in which the reactants had very low solubility (tetrahydrofuran and dichloromethane). Density functional theory (DFT) computed enthalpies correlate to regioselectivity being kinetically driven because the less stable O-isomer forms in higher yield than the more stable N-isomer. Once formed these compounds did not interconvert thermally or undergo a unimolecular ?walk? rearrangement. Mechanistic rationale for the factors underlying the regioselective alkylation of pterins is suggested, where kinetic rather than thermodynamic factors are key in the higher yield of the O-isomer. Computations also predicted greater solubility and reduced triplet state energetics thereby improving the properties of the alkylated pterins as 1 O 2 sensitizers. Insight on thermal and photostability of the alkylated pterins is also provided.